2016
DOI: 10.1002/2015ja021966
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a rapid dropout event for highly relativistic electrons with the RBE model

Abstract: A flux dropout is a sudden and sizable decrease in the energetic electron population of the outer radiation belt on the time scale of a few hours. We simulated a flux dropout of highly relativistic >2.5 MeV electrons using the Radiation Belt Environment model, incorporating the pitch angle diffusion coefficients caused by electromagnetic ion cyclotron (EMIC) waves for the geomagnetic storm event of 23–26 October 2002. This simulation showed a remarkable decrease in the >2.5 MeV electron flux during main phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 88 publications
0
23
0
Order By: Relevance
“…But as showed in our events, it is difficult to obtain the global distribution of EMIC waves from satellites in space. In addition, the statistical EMIC wave distribution achieved from long‐term observations may not realistically represent the wave conditions during a specific event (Kang et al, ). Recently, Y. Zhang et al () developed a new technique to infer EMIC wave amplitudes from the ratio of precipitated and trapped proton fluxes measured by NOAA‐POES satellites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But as showed in our events, it is difficult to obtain the global distribution of EMIC waves from satellites in space. In addition, the statistical EMIC wave distribution achieved from long‐term observations may not realistically represent the wave conditions during a specific event (Kang et al, ). Recently, Y. Zhang et al () developed a new technique to infer EMIC wave amplitudes from the ratio of precipitated and trapped proton fluxes measured by NOAA‐POES satellites.…”
Section: Discussionmentioning
confidence: 99%
“…But as showed in our events, it is difficult to obtain the global distribution of EMIC waves from satellites in space. In addition, the statistical EMIC wave distribution achieved from long-term observations may not realistically represent the wave conditions during a specific event (Kang et al, 2016). Recently, Y.…”
Section: Discussionmentioning
confidence: 99%
“…Such wave candidates include whistler-mode chorus, plasmaspheric hiss, and electromagnetic ion cyclotron (EMIC) waves, whereas these wave modes tend to predominantly resonate with radiation belt electrons at different energies from~1 keV to 10 MeV. A recent simulation of Kang et al [2016], on the basis of the Radiation Belt Environment (RBE) model , demonstrated that EMIC waves can cause efficient electron flux dropouts in the heart of the radiation belt within a short time period. Xiang et al [2016] looked into multisatellite simultaneous observations of magnetopause and atmospheric losses of radiation belt electrons during an event Journal of Geophysical Research: Space Physics 10.1002/2016JA023067 of intense solar wind dynamic pressure pulse.…”
Section: Discussionmentioning
confidence: 99%
“…To examine possible magnetopause shadowing, we investigate drift shells using CIMI with the TS04 model. Drift shells are calculated finding the iso‐contours of the Hamiltonian H at a given time as done by Min et al (, ) using H=E0()E0+2MBm+qnormalΦ, where Φ is the electrostatic potential that we omit as done in Kang et al (). This approximation is valid because convective potentials are much less than 226 keV for this particular event and therefore do not change drift shells significantly; this results in drift shells that are simply a function of B m only.…”
Section: Cimi Simulation Of the Dropoutmentioning
confidence: 99%